An electronic patient-reported outcome tool for the FACT-B (Functional Assessment of Cancer Therapy-Breast) questionnaire for measuring the health-related quality of life in patients with breast cancer: Reliability Study - Matthies, Lina; Keilmann, Lucia; Schneeweiss, Andreas; Sickenberger, Nina; Wallwiener, Stephanie; Feißt, Manuel; Schütz, Florian; Sohn, Christof; Wallwiener, Markus (JMIR medical education)
Background: The most frequent malignant disease in women is breast cancer. In the metastatic setting, quality of life is the primary therapeutic goal, and systematic treatment has only a limited effect on survival rates; therefore, the concept of the health-related quality of life (HRQoL) and measurement of patient-reported outcomes (PROs) are gaining more and more importance in the therapy setting of diseases such as breast cancer. One of the frequently used questionnaires for measuring the HRQoL in patients with breast cancer is the Functional Assessment of Cancer Therapy-Breast (FACT-B). Currently, paper-based surveys still predominate, as only a few reliable and validated electronic-based questionnaires are available. ePRO tools for the FACT-B questionnaire with proven reliability are missing so far. Objective: The aim of this study was to analyze the reliability of tablet-based measurement of FACT-B in the German language in adjuvant (curative) and metastatic breast cancer patients. Methods: Paper- and tablet-based questionnaires were completed by a total of 106 female adjuvant and metastatic breast cancer patients. All patients were required to complete the electronically based (ePRO) and paper-based version of the FACT-B. A frequency analysis was performed to determine descriptive sociodemographic characteristics. Both dimensions of reliability (parallel forms reliability using Wilcoxon test and test of internal consistency using Spearman ρ) and agreement rates for single items, Kendall tau for each subscale, and total score were analyzed. Results: High correlations were shown for both dimensions of reliability (parallel forms reliability and internal consistency) in the patients’ response behavior between paper-based and electronically based questionnaires. Regarding the reliability test of parallel forms, no significant differences were found in 35 of 37 single items, while significant correlations in the test for consistency were found in all 37 single items, in all 5 sum individual item subscale scores, as well as in total FACT-B score. Conclusions: The ePRO version of the FACT-B questionnaire is reliable for patients with breast cancer in both adjuvant and metastatic settings, showing highly significant correlations with the paper-based version in almost all questions all subscales and the total score. [J Med Internet Res 2019;21(1):e10004]